Seismic structure and anisotrophy in southern Africa's lithosphere : constraints from broad-band surface-wave dispersion - Adam, Joanne M.-C. (Trinity College (Dublin, Ireland). Department of Geology, 2013)
Southern Africa contains some of the oldest crust on Earth, with the Archean Kaapvaal Craton bordered to the North by the Archean-Paleoproterozoic Limpopo belt. To understand the mechanisms of deformation of the Archean craton during and since their formation, I mapped the anisotropic structure of their lithosphere that preserved a record of this deformation. I measured surface-wave dispersion curves between station pairs across this region and merged them into subsets characterizing four sub-regions within southern Africa. I obtained accurate dispersion curves for each subset in broad period ranges and inverted them for robust profiles of shear velocity and azimuthal anisotropy spanning the depth range from the upper-crust to the asthenosphere.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin